A unified approach to comparative statics puzzles in experiments - Armin Schmutzler (University of Zurich, Socioeconomic Institute, 2008)
The paper shows that, in some important respects, the differences between the Nash equilibrium and competing concepts such as the quantalresponse equilibrium are smaller than they appear. I start from the observation that, in many experiments, parameter shifts that leave the Nash equilibrium unchanged affect behavior. I explain the direction of change with a heuristic structural approach, relying on properties such as strategic complementarities and increasing differences. I justify the approach using existing comparative statics results for the Nash equilibrium and new comparative statics results for the quantal response equilibrium. Further, I show that the experimental observations can also be rationalized by a model of adjustment to change that does not rely on any equilibrium concept. Finally, I relate the structural approach to equilibrium selection concepts.
Keywords: 330; Nash-Gleichgewicht; Test; Verhaltensökonomik